2022
DOI: 10.3390/ijerph19031105
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in the Heavy Metal Contamination of Urban Soil in the Southeastern United States

Abstract: (1) Background: Field monitoring data for addressing the disproportional burden of exposure to soil contamination in communities of minority and low socioeconomic status (SES) are sparse. This study aims to examine the association between soil heavy metal levels, SES, and racial composition. (2) Methods: A total of 423 soil samples were collected in the urban areas of eight cities across six Southern states in the U.S., in 2015. Samples were analyzed using inductively coupled plasma–mass spectrometry (ICP–MS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
0
18
0
1
Order By: Relevance
“…Overcoming the previous lack of knowledge of the presence of pollution or its harmful effects, current residents are realizing the extent of the continuous exposure to pollutants and how that exposure has affected their health and daily quality of life. This awareness reflects current trends in environmental justice research [ 4 ], as well as known environmental racial disparities in the southeastern US region [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Overcoming the previous lack of knowledge of the presence of pollution or its harmful effects, current residents are realizing the extent of the continuous exposure to pollutants and how that exposure has affected their health and daily quality of life. This awareness reflects current trends in environmental justice research [ 4 ], as well as known environmental racial disparities in the southeastern US region [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 72%
“…Unfortunately, because this industrial pollution is linked to poor health outcomes, such as asthma, dysfunctional lungs, cardiovascular and respiratory illnesses, and low birth weight for babies, environmental justice remains an important issue for communities of color [ 9 ]. Although numerous research studies document the correlation between race, class, and the effects of pollution exposure, decision makers have been unresponsive, making few changes in the siting or regulation of noxious industries [ 5 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the first factor, Pb, Cd, Sb, and As were grouped together, possibly associated with industrial and traffic-related exposures (Figure ). , The second factor was predominantly composed of Ni and Mn. We hypothesize this factor is a marker related to the nearby oil drilling site, as higher levels of Ni and Mn have been observed near oil drilling sites in Los Angeles .…”
Section: Resultsmentioning
confidence: 99%
“…Using NMF, we found that the toenail metal concentration data grouped into three factors, which are consistent with known exposures related to industrial sources, oil drilling, and dietary exposures, which may represent three main sources in this urban environmental justice community. Factor 1, consisting of Pb, Cd, Sb, and As, may represent traffic or industrial pollution from historical sources that continues to contaminate the soil and dust. , We observed higher levels of the industrial factor among children. Factor 2 consists predominantly of Mn and Ni and may be related to the nearby active oil drilling site .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation